Konsep Kafa’ah dalam Prespektif Teori ASyA-Sense - Liddinillah, M Yakhsyallah; Sucipto, Imam (PT. Sharia Journal and Education Center, 2026)
This study aims to analyze the concept of kafa’ah in Islamic family law and reconstruct it through the ASyA-Se (Sense) approach integrated with the MILES mindset (Money, Intelligence, Location, Education, Status). Traditionally, kafa’ah is understood as compatibility between prospective spouses in aspects such as religion, lineage, social status, and economic condition, intended to maintain marital harmony. However, in the contemporary context, this classical framework is considered insufficient to address the complexity of modern family issues, which are increasingly influenced by psychological factors, mindset differences, and interpersonal skills. This research employs a qualitative approach with a normative (library) research method, analyzing Qur’anic verses, Prophetic traditions, and classical juristic views across different schools of thought, supported by relevant academic literature. The findings indicate that kafa’ah is an ijtihād-based construct that is flexible in nature and not a legal requirement for the validity of marriage, but rather a consideration for maintaining family stability. The reconstruction through the ASyA-Se approach based on MILES produces a new understanding of kafa’ah as a multidimensional compatibility encompassing financial mindset (Money), intellectual capacity (Intelligence), socio-cultural environment (Location), educational orientation (Education), and social role/status (Status), all integrated within the framework of maqāṣid al-sharī‘ah. This approach emphasizes value sensitivity, emotional maturity, and alignment of mindset as central elements in determining compatibility between spouses. Therefore, this study contributes theoretically to the development of Islamic family law that is more contextual, humanistic, and adaptive to modern life dynamics, while offering a new paradigm of kafa’ah as a means to achieve a harmonious family characterized by sakinah, mawaddah, and raḥmah.